Atomic Insights of Iron Doping in Nickel Hydroxide Nanosheets for Enhanced Oxygen Catalysis to Boost Broad Temperature Workable Zinc−Air Batteries. Issue 24 (22nd October 2019) - Yang, Rui; An, Li; Zhang, Yu; Zhang, Nan; Dai, Tengyuan; Xi, Pinxian
Abstract: Exploring robust and low‐cost bifunctional oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) electrocatalysts is of great importance for zinc−air batteries (ZABs). Here, we report a controllable Fe‐doping strategy to promote OER/ORR catalytic performance of Ni(OH)2 . The results reveal that Ni1‐x Fex (x=0, 0.05, 0.1, 0.15, 0.2, and 0.25) hydroxide nanosheets (NSs) display a volcano‐like OER performance, with Ni0.8 Fe0.2 NSs being the most optimal OER catalyst, showing an overpotential of 250 mV at 20 mA cm −2 and excellent stability in 1 M KOH. Compared with pristine Ni(OH)2 NSs, the enhanced OER/ORR performance of Ni0.8 Fe0.2 NSs can be attributed to the much more exposed edge sites and oxygen vacancies. Importantly, the rechargeable ZABs built by Ni0.8 Fe0.2 NSs can offer excellent charge‐discharge cycling stability not only under 25 °C, but also both the low temperature (−10 °C) and high temperature (40 °C). The work provide a new way to design highly efficient air‐electrode catalysts with broad working temperature. Abstract : The Ni0.8 Fe0.2 NSs grown on CFP with more oxygen vacancies and more edge sites compared with the pristine Ni(OH)2 NSs was obtained by one‐step hydrothermal method. These defects promote the catalytic performance of both OER and ORR. The RZAB built by Ni0.8 Fe0.2 NSs exhibits good charge‐discharge cycling stability under broad working temperature (−10 °C∼40 °C).